2014
DOI: 10.1089/scd.2013.0309
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Expression Analysis of Regulatory Genes in the Early Developing Human Neural Tube

Abstract: Studies in model organisms constitute the basis of our understanding of the principal molecular mechanisms of cell fate determination in the developing central nervous system. Considering the emergent applications in stem cell-based regenerative medicine, it is important to demonstrate conservation of subtype specific gene expression programs in human as compared to model vertebrates. We have examined the expression patterns of key regulatory genes in neural progenitor cells and their neuronal and glial descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 67 publications
7
46
1
Order By: Relevance
“…The cells separated into 10 distinct clusters. As expected, the majority of the cells at these early developmental timepoints were RG and FPP, in agreement to what was observed in the study by La Manno et al However, three distinct neuronal subtypes were also detected: DA neurons, OTN neurons, which are formed in VM, and a small population of serotoninergic neurons, known to be located in close proximity to DA neurons during development [22]. Moreover, already at these early developmental stages, DA neurons/progenitors of molecularly distinct identities were present, suggesting an early emergence of molecular sub-identities.…”
Section: Discussionsupporting
confidence: 91%
“…The cells separated into 10 distinct clusters. As expected, the majority of the cells at these early developmental timepoints were RG and FPP, in agreement to what was observed in the study by La Manno et al However, three distinct neuronal subtypes were also detected: DA neurons, OTN neurons, which are formed in VM, and a small population of serotoninergic neurons, known to be located in close proximity to DA neurons during development [22]. Moreover, already at these early developmental stages, DA neurons/progenitors of molecularly distinct identities were present, suggesting an early emergence of molecular sub-identities.…”
Section: Discussionsupporting
confidence: 91%
“…Comparative studies of mouse and human development have demonstrated that the same transcription factors drive similar phenotypic pattern generation during neural tube formation between the two species 11 . The key signaling molecules that are necessary to induce V2a interneuron differentiation are retinoic acid (RA), a Sonic Hedgehog (Shh) agonist, and a γ-secretase inhibitor to impede Notch signaling.…”
Section: Development Of the Protocolmentioning
confidence: 99%
“…Additionally, mouse NbM was found to express Nr4a2 (Nurr1) ( Figure 1D), a nuclear receptor required for mDA neuron development (Zetterström et al, 1997). While expression levels of NR4A2 were lower in human NbM, histological analysis of the developing human VM has shown that NR4A2 is present in tyrosine hydroxylase-negative (TH − ) neuroblasts in the floor plate and TH + mDA neurons in the VM (Marklund et al, 2014). The same expression pattern of Nr4a2 can also be seen in histological analysis of the mouse developing midbrain (Villaescusa et al, 2016), indicating that in both the human and mouse VM, NbM differentiate into mDA neurons.…”
Section: Human Vm Post-mitotic Cellsmentioning
confidence: 99%
“…Furthermore, human mDA neuron development also appears to follow a similar sequence of events to that of murine mDA neuron development. For instance, the human midbrain floor plate is defined by the expression of LMX1A and FOXA2, with the FOXA2 domain extending further laterally into the basal plate (Nelander et al, 2009;Marklund et al, 2014). Moreover, in the VZ of the human floor plate, the pro-neural factor NEUROG2 overlaps with the expression of LMX1A, and in the IZ and MZ, cells expressing key determinants of post-mitotic mDA neurons, NR4A2, PITX3, and TH, can be observed (Nelander et al, 2009).…”
Section: Introductionmentioning
confidence: 99%